Let $V$ be an $n$-dimensional vector space over a field $F$ (the characteristic of which, for the purpose of this post, may be taken as $0$). Let $T$ be a linear operator on $V$ and $\lambda\in F$.

Sometime ago, somewhere (I can't recall where) I read that

Formula. $\det(T-\lambda I)= \sum_{k=0}^n (-1)^k \text{trace}(\Lambda^k T)\lambda^{n-k}$

I considered a special case to test this out by taking $n=3$. And here is what I got:

Let $\{e_1, e_2, e_3\}$ form a basis for $V$. Then $$\det(T-\lambda I)(e_1\wedge e_2\wedge e_3)=(Te_1-\lambda e_1)\wedge (Te_2-\lambda e_2)\wedge (Te_3- \lambda e_3)$$

whence expanding the RHS we get

$$(\det T)(e_1\wedge e_2\wedge e_3) - \lambda(Te_2\wedge Te_2 \wedge e_3+ Te_1\wedge e_2\wedge Te_3 + e_1\wedge Te_2\wedge Te_3)+\lambda^2(Te_1\wedge e_2\wedge e_3+ e_1\wedge Te_2\wedge e_3+e_1\wedge e_2 \wedge Te_3) - \lambda^3(e_1\wedge e_2\wedge e_3)$$

Since $\det T=\text{trace}(\Lambda^3 T)$, the coefficient of $\lambda^0$ matches with that in the formula. Also, the coefficient of $\lambda^2$ is just $\text{trace}(T)$ by definition so this is also fine.

The Problem. What I am not able to see is how the coefficient of $\lambda$ eaul to $\text{trace}(\Lambda^2T)$.

Can somebody please help. Thanks.

  • $\begingroup$ Your formula uses $\lambda$ and $x$ to mean the same thing. Also, it may be helpful to first consider the case when the $e_i$ are a basis of eigenvectors for $T$ and recall Vieta's formulas about the roots of polynomials. $\endgroup$ – Nate Jan 28 '16 at 17:54
  • $\begingroup$ I am sorry about the $x$. I meant $\lambda$. Let me edit. $\endgroup$ – caffeinemachine Jan 28 '16 at 17:58
  • 1
    $\begingroup$ What a beautiful formula! I've never see that particular one before. $\endgroup$ – Cheerful Parsnip Jan 28 '16 at 18:07

Let us write $Te_i = \sum_j a^j_i e_j$. For $1 \leq i < j \leq n$, we have

$$ (\Lambda^2(T))(e_i \wedge e_j) = Te_i \wedge Te_j = \left( \sum_{k_1} a_i^{k_1} e_{k_1} \right) \wedge \left( \sum_{k_2} a_j^{k_2} e_{k_2} \right) = (a_i^i a_j^j - a_i^j a_j^i) (e_i \wedge e_j) + \cdots $$

where the $\cdots$ don't involve $e_i \wedge e_j$ (as the coefficient of $e_i \wedge e_j$ for $i < j$ comes from $k_1 = i, k_2 = j$ or $k_1 = j, k_2 = i$). Hence,

$$ \mathrm{tr}(\Lambda^2T) = \sum_{i < j} (a_i^i a_j^j - a_i^j a_j^i). $$

In your case, similar arguments show that

$$ Te_1 \wedge Te_2 \wedge e_3 = \left( \sum_{k_1} a_1^{k_1} e_{k_1} \right) \wedge \left( \sum_{k_2} a_2^{k_2} e_{k_2} \right) \wedge e_3 = (a_1^1 a_2^2 - a_1^2 a_2^1) (e_1 \wedge e_2 \wedge e_3), \\ Te_1 \wedge e_2 \wedge Te_3 = \left( \sum_{k_1} a_1^{k_1} e_{k_1} \right) \wedge e_2 \wedge \left( \sum_{k_2} a_3^{k_2} e_{k_2} \right) = (a_1^1 a_3^3 - a_1^3 a_3^1) (e_1 \wedge e_2 \wedge e_3), \\ e_1 \wedge Te_2 \wedge Te_3 = e_1 \wedge \left( \sum_{k_1} a_2^{k_1} e_{k_1} \right) \wedge \left( \sum_{k_2} a_3^{k_2} e_{k_2} \right) = (a_2^2 a_3^3 - a_2^3 a_3^2) (e_1 \wedge e_2 \wedge e_3), $$

and so indeed

$$ \mathrm{trace}(\Lambda^2 T)(e_1 \wedge e_2 \wedge e_3) = Te_1 \wedge Te_2 \wedge e_3 + Te_1 \wedge e_2 \wedge Te_3 + e_1 \wedge Te_2 \wedge Te_3. $$

  • $\begingroup$ Thank you. Do you see how to establish the corresponding statement for $\text{trace}(\Lambda^k T)$? $\endgroup$ – caffeinemachine Jan 31 '16 at 16:34
  • $\begingroup$ For the more general case, it is useful to use the Hodge star construction. Put an inner product on $V$ and choose an orthonormal basis $(e_1, \ldots, e_n)$. Then we have $\mathrm{tr}(\Lambda^kT) (e_1 \wedge \cdots \wedge e_n) = \left( \sum_{I}^{'} \left< (\Lambda^k(T))(e_I), e_I \right> \right) e_1 \wedge \cdots \wedge e_n = \sum_{I}^{'} \Lambda^k(T)(e_I) \wedge (*e_I)$. $\endgroup$ – levap Jan 31 '16 at 17:24
  • $\begingroup$ Can you please frame this as an answer here math.stackexchange.com/questions/1634778/… $\endgroup$ – caffeinemachine Jan 31 '16 at 17:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.